Content Differentiation: An Adaptive Strategy to Enhance High School Students’ Participation and Learning Outcomes in Chemistry - Satifa Ananda Yulian; Maasje Catherine Watulingas; Farah Erika (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2025)
Learning difficulties among students can be caused by various factors, such as differences in interest, intelligence, talent, motivation, and cognitive abilities. This diversity requires teachers to implement adaptive learning strategies, one of which is content differentiation. This study aims to determine the effect of implementing a content differentiation strategy on students' learning outcomes in the colloid topic. The research employed a true experimental design with a post-test only control group design. The population consisted of 12th-grade students at SMA Negeri 8 Samarinda, selected through total sampling. The sample included 70 students, divided into experimental and control classes. Data collection instruments included a learning outcome test and student activity observation. Data were analyzed using the Mann-Whitney test. The results showed that the average score of the experimental class (90.8) was higher than that of the control class (87.2), with a significance value of 0.029 (p < 0.05), indicating a significant impact.